IMPROVEMENT OF ENGLISH PRAGMATIC COMPETENCE OF AL-GHOZALI HIGH SCHOOL STUDENTS - Mia Perlina; Hilma Safitri; Ni Komang Ariani (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2023)
The aim of this community service was to improve students’ English pragmatic competence. The problem of the students found in SMA Al-ghozali was that they often misunderstood the implicit meaning of words. Hence, the students needed to be given a training related to learning English pragmatics. This PkM activity involved 31 students of Al-Ghozali High School located at Jalan Permata No. 19 RT. 06 RW 05, Curug, Gudung Sindur, Bogor, West Java. The stages of training in PkM activities consisted of (1) planning, (2) implementation, and (3) evaluation. At the planning stage, three lecturers and five students of Pamulang University involved prepared a learning method and pre-test. At the implementation stage, the students of Pamulang University provided a training by presenting materials and conducting a discussion on a topic of Implicature. The students collaborated to complete the exercises given by the students of UNPAM team. They carried out correction activity accompanied by the students of UNPAM.  The students then  competed to answer questions  by using  games  in  order  to  create  a  fun  learning  atmosphere.  At the evaluation stage, the students carried out post-test. The students of UNPAM concluded the lesson and closed the training session at the end of the training. The average scores of the pre-test and post-test increased from 48.1 to 72.9 or 51.5 %. It can be said that the students’ English Pragmatics competency increases.